Pengembangan Media Pembelajaran Berbasis Game Educaplay pada Pelajaran PAI Materi Ibadah Haji di Sekolah Dasar - Baiti Al Ami; Raharjo Raharjo (Universitas Negeri Surabaya, 2025)
This study aims to develop and test the effectiveness of Educaplay game-based learning media on the subject of Hajj worship in Islamic Education learning in elementary schools. The research method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data collection was carried out through questionnaires, interviews, observations, and tests. The validation results by media and content experts showed percentages of 94% and 93.3%, both of which fall into the very good category. Student learning outcomes were analyzed by comparing pretest and posttest scores. The average pretest score was 74.50, increasing to 91.50 in the posttest. Based on the N-Gain test, a score of 0.66 or 66% was obtained, categorized as medium. This indicates that the Educaplay game-based learning media is effective in improving student learning outcomes in the subject of Hajj worship.